Incidence of COVID-19 Vaccination-Related Uveitis and Effects of Booster Dose in a Tertiary Uveitis Referral Center - Chew, Milton C.; Wiryasaputra, Shaan; Wu, Meihui; Khor, Wei Boon; Chan, Anita S. Y. (Frontiers in Medicine, 2022)
Background: We report vaccine and booster-induced uveitis in Singapore, a country with high vaccination and booster rates to highlight the differences and potential role of prophylactic treatment for sight-threatening infectious uveitis. Methods: Clinical data extracted from the de-identified uveitis database in Singapore National Eye Center. Six patients (8 eyes) developed uveitis within 14 days after undergoing COVID-19 vaccination (primary and/or booster). Results: All patients received 2 doses of COVID-19 vaccination. 1.39% (6/431) develop COVID19 vaccine-related uveitis. 50% (3/6) with non-infectious anterior uveitis (NIAU) presented with a non-granulomatous anterior uveitis (AU). The remaining (3/6) presenting with a granulomatous AU were diagnosed with reactivation of cytomegalovirus, varicella-zoster virus and toxoplasma chorioretinitis respectively. All patients responded to definitive treatment specific to their diagnosis. The mean visual acuity at presentation was 0.36 ± 0.20 logMAR and improved to 0.75 ± 0.09 (p=0.009). Mean time from vaccination to uveitis was 9.7 (range: 3 – 14) days. All patients developed uveitis after second vaccination dose. 16.67% (1/6) patients had a recurrence after the third booster dose. None of the 3 patients with infectious uveitis developed recurrence but had received maintenance therapy up to or during the booster. Conclusion: Uveitis after COVID-19 vaccination is rare. In our series, there is a trend to suggest that infectious uveitis may also contribute to COVID-19 vaccination-related uveitis in addition to NIAU. With definitive treatment, all cases were self-limited without systemic sequelae. Prophylactic treatment during booster vaccine may prevent reactivation of sight-threatening infections and reduce morbidity although risk-benefits should be considered for individual patients given the low rate of occurrence.